Vacation or Validation: Liburan sebagai Bentuk Validasi dan Pencitraan melalui Media Sosial di Kalangan Generasi Z - Asyraf, J. A (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to identify how holidays and tourism activities are used by Generation Z as a means of self-validation and personal branding through social media. The method used is qualitative descriptive with a social media observation approach and in-depth interviews with participants aged 18–25 who actively publish holiday content on Instagram and TikTok. The results show that the beauty of tourist destinations is no longer judged solely by physical experience, but rather by how